Larvicidal, Pupicidal, Oviposition Deterrent Activity And Smoke Toxicity Of Mature Leaf Extracts Of Annona Reticulata Linn. Against Filarial Vector Culex Quinquefasciatus Say - SUBRATA MALLICK; GOUTAM CHANDRA (International Journal of Pharma and Bio Sciences, 2015)
Crude and ethyl acetate extracts of mature leaves of Annona reticulata Linn. (A. reticulata) were investigated to establish their biocontrol potentialities under laboratory condition against larvae (different instars) and pupae of Culex quinquefasciatus Say, 1823 (Cx. quinquefasciatus) at different concentrations. Crude as well as ethyl acetate extracts showed excellent larvicidal activity at remarkable low concentrations. Oviposition deterrent activity of ethyl acetate extract and smoke toxicity effect of mature leaf powdered coils on adult mosquitoes were also examined and showed an excellent result. Pupae also showed motality at low concentrations. LC50 and LC90 values of larvicidal and pupicidal activity gradually decreased with increased exposure period. Statistical justifications were done through Log-probit, regression and ANOVA analyses. No adverse effect has been found on tested non target organisms. Photochemical analyses of leaf extracts revealed the presence of different secondary metabolites. So, crude and ethyl acetate leaf extracts of A. reticulata can effectively be used as larvicide, pupicide, oviposition deterrent activity and smoke toxicity against Cx. quinquefasciatus mosquito species.